Reviews - Robinson, D.; Larsson, Lars; Otto, Poul; Stoklund, M. (Journal of Danish Archaeology, 1991)
Reviews: W. van·Zeist, K. Wasylikowa & K.-E. Behre ( eds.): Progress in Old World Palaeoethnobotany (by D. Robinson) A. D. Johasson: Barmosegruppen (by L. Larsson) Ian Hodder: The Domestication of Europe (by P. O. Nielsen) B. Oldenstedt: On the Origin and Early History of the Runic Script (by M. Stoklund)